MRAC Control for Temperature Regulation of Dodol Processes - Muhamad Ghazali, Imran; Hamdan, Rohaiza; A. Jalil, Mohd Hafiz (Evolution in Electrical and Electronic Engineering, 2023)
Dodol is a traditional Malaysian cuisine that has a sticky consistency and sweet flavour. In order to cook it a person needs to control the temperature of the fire to make sure the dodol is not burnt and has the correct consistency. Adaptive control has long been yearned to be implemented in control systems. With the implementation of adaptive control, a system can regulate itself without any assistance from an operator or user. Besides that, it functions using a closed-loop system and the system can regulate itself with the designated input and output. The system will trace back and feedback on the signal if there is any error detected and will compare it to the reference model until there is no error so the system will maintain almost perfect efficiency when operating. In this project Model Reference Adaptive Control (MRAC) is implemented into a dodol-making machine for temperature regulation. The transfer function from the dodol plant is modeled using Autoregressive Exogenous Variables (ARX) method using System Identification Toolbox. The performance of the MRAC system is analysed and compared to Proportional Integral Derivative (PID) controller to see which controller is better in terms of rise time, settling time, and overshoot value. Based on the comparative study done, the MRAC controller has better rise time, settling time, and overshoot value compared to the PID controller which are 207.784s, 561.412s, 0.500%, and 334.933s, 1606.311s, 4.737% respectively for each controller. Overall, the MRAC controller is proven stable and can be proceeded with real-time testing.